Implementation of Environmental Care Character Education Based on Community Service - Izzati, Nurul; Kusumaningsih, Widya; Sulianto, Joko (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the implementation of environmental character education based on community service through the SULAPAT Mengabdi program at Sultan Agung 4 Islamic Elementary School, Semarang City. The background of this study is based on the urgency of strengthening environmental character since the elementary school level as a response to various increasingly complex ecological problems. The study uses a qualitative approach with a phenomenological method to deeply explore the experiences, perceptions, and real practices of education actors in implementing the program. The research subjects included the principal, teachers, students, parents, and the surrounding community, who were actively involved in the activities. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and continuous conclusion drawing. The results of the study indicate that the SULAPAT Mengabdi program is implemented systematically, organized, and collaboratively through real activities such as community service, mosque cleaning, environmental cleanup, and community social actions. The direct involvement of students in these activities has been proven to be able to gradually foster responsibility, social empathy, cooperation, religiosity, and ecological awareness. A monitoring system using control cards and classroom reflections strengthens the process of internalizing values and changing student behavior. This research confirms that environmental character education will be more effective when designed contextually, based on direct experience, and involving ongoing synergy between schools, families, and the community.